2019
DOI: 10.1080/09669582.2019.1619748
|View full text |Cite
|
Sign up to set email alerts
|

A critical framework for interrogating the United Nations Sustainable Development Goals 2030 Agenda in tourism

Abstract: Research in the area of sustainable tourism continues to grow, however a lack of understanding regarding necessary action inhibits progress. McCloskey's (2015) critique regarding the failure of the MDGs, as a direct result of a lack of critical consciousness, and understanding of the structural contexts of poverty and under-development, provided the impetus for our work. McCloskey (2015) signals the important role of education in fostering transitions to sustainability. As such, we have applied our critical le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
131
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(172 citation statements)
references
References 77 publications
1
131
0
8
Order By: Relevance
“…In Iran this is particularly significant for women's economic empowerment which is central to realizing women's rights and gender equality and to the achievement of the SDGs (UN Women, 2020). While, tourism has been viewed as a sector capable of advancing gender equality and women's empowerment (Alarc on & Cole, 2019;Cole, 2006;Tucker & Boonabaana, 2012) as it is also enshrined in SDG5 which focuses on gender equality and women's empowerment (Boluk et al, 2019), nonetheless, as the findings of this study also showed, the economic disruption ensuing from sanctions are detrimental to such empowerment capacity of tourism.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In Iran this is particularly significant for women's economic empowerment which is central to realizing women's rights and gender equality and to the achievement of the SDGs (UN Women, 2020). While, tourism has been viewed as a sector capable of advancing gender equality and women's empowerment (Alarc on & Cole, 2019;Cole, 2006;Tucker & Boonabaana, 2012) as it is also enshrined in SDG5 which focuses on gender equality and women's empowerment (Boluk et al, 2019), nonetheless, as the findings of this study also showed, the economic disruption ensuing from sanctions are detrimental to such empowerment capacity of tourism.…”
Section: Discussionmentioning
confidence: 72%
“…As such, this study shows that sanctions imposed by major powers on, usually developing countries negatively affect the peace-building capacity of tourism and in turn generate more depression and conflict. Furthermore, if we take another step back, we can observe that not only is the impositions of sanctions on Iran and its subsequent implications for the Iranian people steeped in politics but so too is the very framing of the notion of tourismthrough-peace (Blanchard & Higgins-Desbiolles, 2013b;Cho, 2007 ) and, we would also suggest, the SDGs (Boluk et al, 2019;Hall, 2019).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Jones and Wynn 2019) and frameworks (e.g. Boluk et al 2019) used to analyse sustainability. Within the hospitality industry the concept of sustainability has also been applied to a range of natural disasters and emergencies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…En la actualidad los debates en torno a la agenda de turismo respecto al desarrollo sostenible, discuten sobre las debilidades y la falta de acciones claras para conseguir los objetivos hasta el 2030. Por una parte, es evidente una falta de incentivos para la especialización de técnicos con enfoque en desarrollo del turismo sostenible, pero por otra, preocupa la falta de participación de las mujeres, problemas con un consumo ético de productos, la falta de inclusión de los saberes ancestrales aplicados al desarrollo y modelos de gobernanza más integrales (Boluk, Cavaliere y Higgins, 2019). Por esto, urge la investigación en cuanto al desarrollo del pensamiento crítico de todos los actores en relación a nuevas formas de economías, redistribución de poder, equidad y conservación biocultural.…”
Section: A Desarrollo Del Turismo Sostenibleunclassified